Liquid Nanoco2 with Kaigen and GEIOS Technologies with Thermal and Rheological Characterization of Graphene Oxide/Carbon Nanotube Hybrid Nanoparticle-Enhanced Liquid CO2 for District Cooling and Data Centers Applications, (International Journal of Scientific Research and Management (IJSRM), 2025)
This study presents a comprehensive thermal and rheological characterization of a novel hybrid nanofluid consisting of liquid carbon dioxide (CO₂) enhanced with graphene oxide (GO) and carbon nanotubes (CNTs). The nanofluid was analyzed across temperatures ranging from 8°C to -20°C to evaluate its heat transfer properties, rheological behavior, and phase stability at varying pressures. Results indicate a significant enhancement in thermal conductivity (approximately 77% improvement over pure liquid CO₂) while maintaining favorable flow characteristics with minimal viscosity increase. Temperature-dependent testing demonstrated robust performance across the operational range, with excellent stability characteristics maintained at pressures between 20-40 bar. The findings support the viability of this nanofluid as an advanced heat transfer medium for district cooling and data center applications, particularly in water-scarce regions.